Gambaran Pengetahuan Ibu Hamil tentang Perawatan Payudara Selama Kehamilan di Puskesmas Karang Rejo Tarakan - Apriorita Apriorita; Rohandi Baharuddin; Sriargianti Amir; Satria Hanggara Putra (Journal Borneo, 2023)
Breast care is an important intervention during pregnancy as preparation for breastfeeding after delivery. Based on the results of preliminary studies, some mothers do not know how to care for their breasts. The purpose of this study was to describe the knowledge of pregnant women about breast care during pregnancy. This research method is descriptive, taking samples using non-probability sampling using an accidental sampling technique with a total sample of 50 according to the inclusion and exclusion criteria. The data collection technique uses a questionnaire related to breast care knowledge. The results showed that the characteristics of the respondents based on the highest age were 20-35 years old, with 25 (50.0%) respondents. Based on occupation, the most were IRT with 31 (62.0%) respondents, based on parity the highest number and multipara were 28 (56) .0%) of respondents, based on education the highest results were obtained, namely high school as many as 22 (44.0%), based on knowledge obtained good knowledge results as many as 6 (12.0%), enough as many as 16 (32.0%), and less as much 28 (56.0%) respondents. This study’s conclusion shows that most breastfeeding mothers at the Karang Rejo Health Center in Tarakan City are knowledgeable about breast care during pregnancy.